A prática odontológica na perspectiva do terceiro setor: o caso das organizações da sociedade civil de interesse público - Londrina-PR - Alves-Souza, Rosani Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
The invigoration of the civil society in the last three decades has become a valuable option in the process of overcoming the inequalities generated in capitalist crisis. In the conflicting scenery health versus inequalities, the issue of the need for amplification of the access to buccal health for the excluded groups comes as a theme worthy of reflection and committed attention. Different social subjects with different degrees of adhesion have been trying to build an identity of performance in the public and private instances, like in the public non-state institutions, centered in social development. Such a movement around the well-being has been strongly marked by the appearance of countless private initiatives in the creation of juridical entities with public purposes and without profitable ends. Known as the new law of the Third Sector, Law 9790/99 is the basis of the process of regulation of the entities without profitable ends, qualifying them as Organizations of the Civil Society of Public Interest - OSCIPs. This study aims to identify the odontological practice implemented in the ambit of the OSCIPs, in the municipal area of Londrina-PR, with particular interest in the odontological services, seeking to contribute to the process of social recognition of these entities. For such, the process of methodological construction of this study privileged the qualitative descriptive approach, with some recommendations to case studies. Two analytic categories were defined capable to express the dimensions to be apprehended in the process of the study. The results indicated that the studied entities exercise significant influence in the promotion of the access in buccal health, besides placing them as instruments of invigoration of the guarantee of the right to health and social recognition

O fortalecimento da sociedade civil, nas últimas três décadas, tem se configurado como uma opção de valor no processo de superação das desigualdades geradas diante da crise do capitalismo. No cenário do embate saúde versus desigualdades, comparece como tema merecedor de reflexão e atenção compromissada, a questão da necessidade de ampliação do acesso aos grupos excluídos em saúde bucal. Diferentes sujeitos sociais com diferentes graus de adesão têm procurado construir uma identidade de atuação nas instâncias pública e privada, como na pública não-estatal, centrada no desenvolvimento social. Essa movimentação em torno do bem-estar tem sido fortemente marcada pelo surgimento de inúmeras iniciativas privadas na criação de entidades jurídicas, sem fins lucrativos e de finalidade pública. Conhecida como a nova lei do Terceiro Setor, a Lei 9790/99 se firma como base do processo de regulamentação das entidades sem fins lucrativos, qualificando-as como Organizações da Sociedade Civil de Interesse Público ― OSCIPs. Este estudo tem como objetivo identificar a prática odontológica implementada no âmbito das OSCIPs, do município de Londrina-PR, com interesse sobre as de caráter exclusivo de prestação de serviços odontológicos, visando às contribuições ao processo de reconhecimento social dessas entidades. Para tanto, privilegiou-se no processo de construção metodológica a abordagem qualitativa de natureza descritiva com algumas recomendações aos estudos de casos. Foram definidas duas categorias analíticas capazes de expressar as dimensões a serem apreendidas no processo do estudo. Os resultados indicaram que as entidades estudadas exercem significativa influência na promoção do acesso em saúde bucal, além de localizarem-nas como instrumentos de fortalecimento da garantia do direito à saúde e do processo de reconhecimento social
Keywords: Oral health; Desenvolvimento social; Odontologia; Saúde bucal; Associações sem fins lucrativos; Londrina (PR)